Real World Experience with an Optimized Control Scheme for a Ventricular Assist Device - Steingräber Robert (Current Directions in Biomedical Engineering, 2020)
A closed-loop control software for the new mobile Berlin Heart EXCORR driving unit was optimized to balance usability, durability, pump wash out, blood stress and power consumption. The piston of the electro-pneumatic cylinder is moved on a pump-cannula-specific trajectory. A friction and a valve model are adapted online. Verification and real world data show constant flow, low power consumption and the adherence of all limits.